If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 12 + -13 Reorder the terms: 5 + 3x = 12 + -13 Combine like terms: 12 + -13 = -1 5 + 3x = -1 Solving 5 + 3x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = -1 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = -1 + -5 3x = -1 + -5 Combine like terms: -1 + -5 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 4(3x+2)-x=-8x+8 | | -5(1-5x)+5(-8x-2)=14x-8x | | 4(3x+2)-x=11x+11 | | 14-5x=59 | | 7-6u=5u+2y | | -7-7p=-5-p-8-4p | | 4(3x+2)-x=8x+-11 | | (2x+5)*(x+12)*10=5000 | | 5-(9+2c)=12+6(c-6) | | 3a+15=45 | | 3x-9=x-5 | | 5h-3=6-4h | | 168=t^2 | | 2x^2-3y^2-4xy+12=0 | | xy-3x=14 | | -7w+9x+3x+6y+3y+5w= | | 23x+1=180 | | 4x-2(x-1)+3= | | 4(3x+2)-x=-11x-3 | | 2+3x-4xy+7-y-5= | | (1x-4)+3x+4=-4x+24 | | -12=s+6 | | 4(kx-gx)=5 | | 3t+-6=3 | | -12=5+6 | | 4(3x+2)-x=-5x-3 | | -3x+7+4x=3+x+4 | | xy+x=7 | | 4(2x-2)=152 | | 4(3x+2)-x=5x-3 | | 2(y-8)+8y=6y-10 | | q=3q |